Treatment for Dupuytren's disease - Nanchahal, J; Midwood, KS (2013)
Musculoskeletal fibroproliferative disorders, such as Dupuytren's disease may be treated by administering locally a TNF-alpha antagonist. TNF-alpha antagonists find particular utility in inhibiting the progression of early disease state Dupuytren's disease and other musculoskeletal fibroproliferative disorders and, in combination with extracellular matrix degradation agents (such ascollagenase or matrix metalloproteinase I), treating advanced disease state Dupuytren's disease and, in particular inhibiting recurrence.